The Influence of NetFlix Series on English Teachers’ Language Maintenance - Miranda Muge Aisyah; Ali Mustofa; Slamet Setiawan (Universitas Negeri Semarang, 2022)
Netflix series have emerged as a popular culture medium with an impact on the language skills of its audience. To explore the influence of Netflix series on English teachers' language skills, this research utilized a qualitative case study approach. A total of 20 English teachers participated in the study by completing a demographic survey. Participants were selected purposively based on their experience in maintaining language skills using authentic materials, including Netflix series. Data collection involved the use of a questionnaire and interviews. The questionnaire aimed to gather demographic information and elicit participants' perceptions regarding the benefits of watching Netflix series for language skill maintenance. Subsequently, interviews were conducted to obtain in-depth insights into participants' responses from the questionnaire. Five English teachers voluntarily took part in the interview process. Thematic content analysis was employed to analyze the data collected from the questionnaire and interviews. The findings of the study revealed various benefits for English teachers in terms of strengthening their language skills. These benefits included fostering a positive attitude towards teaching, enhancing language proficiency, and improving cultural awareness. The study suggests that watching Netflix series has a profound impact on English teachers' language development. In summary, this qualitative case study highlights the positive influence of Netflix series on English teachers' language skills. The research suggests that incorporating Netflix series into language learning routines can be a valuable tool for English teachers. The study contributes to understanding the potential benefits of utilizing popular media platforms like Netflix for language skill development among educators.